18F-FDG PET/CT Finding of Bilateral Primary Breast Mucosa-Associated Lymphoid Tissue Lymphoma. (February 2015) - Kim, Do-Hoon; Jeong, Ji Yun; Lee, Sang-Woo; Lee, Jaetae; Ahn, Byeong-Cheol
<x xml:space="preserve">Abstract</x> Abstract Primary breast lymphoma is an extremely rare disease. Primary breast mucosa-associated lymphoid tissue (MALT) lymphoma is even rarer, and bilateral involvement is exceptional. We report on the 18F-FDG PET/CT findings in a patient with primary bilateral breast MALT lymphoma. 18F-FDG PET/CT showed hypermetabolic masses in both breasts. The patient was confirmed with bilateral primary breast MALT lymphoma after total mastectomy. Despite its rarity, primary breast MALT lymphoma should be considered in patients with hypermetabolic masses in the breast. If primary breast MALT lymphoma is suspected, 18F-FDG PET/CT is a useful tool for initial staging in patients.